Researching possible futures to guide leaders towards more effective tertiary education - Niki E Davis; Andrew Higgins (Flexible Learning Association of New Zealand, 2015)
This research aimed to inform institutional leaders by producing and disseminating a system wide view of what tertiary education might look like in Aotearoa New Zealand, five years into the future. The researchers were responding to a challenge in a speech at the DEANZ 2010 conference by a highly respected national leader (Dr Peter Coolbear). The outcome became known as the DEANZ2016 scenario set. Using JISC scenario planning methodologies, including interviews of 16 national and international education leaders, the scenario set was developed on an X axis depicting the tension between facing the academy vs facing New Zealand employers, professions and iwi, and a Y axis depicting the tension between standardized education vs customization to personalise learning. Each of the four quadrants aimed to expose and contrast potential future scenarios. These were entitled: Articulation, The 'Supermarket', Quality Branded Consortia, and Self Determination. Innovatively disseminated via the web, the DEANZ2016 website became the most popular section of the larger Ako Aotearoa website, which stimulated further research into uptake and impact of the project.